Transitioning to Climate Resilient Development : Perspectives from Communities in Peru - Sperling, Frank; Validivia, Corinne; Quiroz, Roberto; Valdivia, Roberto; Angulo, Lenkiza; Seimon, Anton; Noble, Ian (World Bank, Washington, DC, 2014)
The livelihoods of communities in rural areas of Peru are predominantly dependent on climate-sensitive sectors such as agriculture. Given their close connection with the environment, the understanding of how these communities perceive risks and how they adapt to and cope with climate hazards is important for identifying entry points for efforts aimed at building resilience. In this context, it is assumed that the successful use of climate information will depend on appropriate information formats that fit the decision-making structure of communities as stakeholders and also have their trust. In connection with collecting information of community knowledge on environmental predictors of weather and climatic conditions and recommendations for capacity-building needs, it is hoped that the report will provide valuable, initial guidance on which elements play an important role in strengthening the adaptive capacity of communities to climate variability and change. The objective of part one is to place climate variability and change into the broader development of Peru and outline risk management structures. This overview will then be contrasted with the perceptions of risks and vulnerabilities and coping and adaptation strategies at the community level described in part two for Northwestern Peru and the altiplano, which are regions considered highly vulnerable to climate-related hazards. The report concludes by developing a set of overarching and locale-specific recommendations.